Statistical analysis of the hydrogeochemical evolution of groundwater in hard rock coastal aquifers of Thoothukudi district in Tamil Nadu, India - Singaraja, C.; Chidambaram, S.; Prasanna, Mohan Viswanathan; Thivya, C.; Thilagavathi, R. (Springer, 2014)
The study of groundwater hydrogeochemistry of a hard rock aquifer system in Thoothukudi district has resulted in a large geochemical data set. A total of 100 water samples representing various lithologies like Hornblende Biotite Gneiss, Alluvium Marine, alluvium Fluvial, Quartzite, Charnockite, Granite and Sandstone were collected for two different seasons and analyzed for major ions like Ca2+, Mg2+, Na+, K+, HCO3 -, Cl-, SO4 2-, NO3 -, PO4 -, F- and H4SiO4. Statistical analysis of the data has been attempted to unravel the hidden relationship between ions. Correlation analyses and factor analyses were applied to classify the groundwater samples and to identify the geochemical processes controlling groundwater geochemistry. Factor analysis indicates that sea water intrusion followed by leaching of secondary salts, weathering and anthropogenic impacts are the dominant factors controlling hydrogeochemistry of groundwater in the study area. Factor score overlay indicate major active hydrogeochemical regimes are spread throughout the Eastern, Northwestern and Southeastern parts of the study area. The dominant ions controlling the groundwater chemistry irrespective of season are Cl-, Na+, Mg2+, Ca2+, SO4 2-, K+ and NO3 -. An attempt has also been made to note the seasonal variation of the factor representations in the study area. This study also illustrates the usefulness of statistical analysis to improve the understanding of groundwater systems and estimates of the extent of salinity/salt water intrusion.